Experimental study on the mechanism of surface damage induced by abrasive particles under heavy-load line-contact sliding-rolling conditions - Yang Li; Wei Wang (PLoS ONE, 2025)
In this study, the JPM-1 contact fatigue testing machine is used to carry out experiments on the mechanism of surface damage induced by abrasive under heavy-load line contact rolling-sliding conditions. In order to be close to the real working conditions, the lubricating oil circuit circulation system is specially designed to ensure that abrasive particles with specific concentration and particle size can continuously circulate in the experiment, so as to simulate the influence of abrasive particles in the lubricating oil on the surface of the friction pair. During the experimental process, with particle size and concentration in the lubricating oil, the rolling-sliding ratio, and the experimental duration as variables, contact fatigue tests are conducted through the coordinated operation of the JPM-1 type testing machine and the lubricating oil circulation system. After the test, KEYENCE VK-X250 series laser microscope is used to observe the surface of the specimen, and combined with 3D topography measurement, the two-dimensional and three-dimensional related parameters are extracted and analyzed. The results show that when the particle size of iron oxide particles increases, the surface roughness and protrusion parameters of the specimen decrease first and then increase, and the volume and number of pits continue to increase. The increase of concentration aggravates the wear, and the roughness parameters, the volume and surface area of the pit convex increase. At the same time, the increase of the slip-roll ratio and the extension of the test time will aggravate the wear, resulting in a significant increase in the coefficient of friction and the amount of wear. This experimental study can provide a reference for the mechanism of surface damage caused by abrasive particles in line contact parts.